Early diagenesis of radium 226 and radium 228 in lacustrine sediments influenced by former mining sites. (October 2020) - Mangeret, Arnaud; Reyss, Jean-Louis; Seder-Colomina, Marina; Stetten, Lucie; Morin, Guillaume; Thouvenot, Antoine; Souhaut, Marc; van Beek, Pieter
Abstract: Radium is a naturally occurring radioactive element commonly found at low levels in natural systems such as lacustrine or marine sediments. Anthropogenic activities including former uranium mining activities can lead to the dissemination of radium isotopes having high radiological toxicities, which potentially threaten the safety of nearby environments. Although radium mobility in oxidized environments is known to be largely governed by sorption/desorption onto Fe and Mn oxyhydroxides and coprecipitation with sulfate minerals (e.g. barite), little is known regarding its behavior under reducing conditions, which are the conditions typically encountered in organic-rich systems such as wetlands and lake sediments. The present study aims at understanding the behavior of long-lived radium isotopes ( 226 Ra and 228 Ra), during early diagenesis of lake sediments contaminated by former uranium mining activities. Solid and pore water concentrations of 226 Ra and 228 Ra were determined using ultra low background gamma spectrometry, which allowed improvement of detection limits and measurement accuracy. This study shows that the downcore distribution of radium isotopes is closely related to the reductive dissolution of iron and manganese oxyhydroxides below the sediment-water interface. The resulting diffusive fluxes of 226 Ra and 228 Ra (4.1 10 −25 and 4.7 10 −28 mol cm −2 .s −1 ) are however significantly lower than other radium-impacted environments, such as uranium mill tailings pond and phosphate industry-impacted sediments, and are similar to those reported for natural marine environments. Hence, in the reduced lake sediments of Saint-Clement, the major fraction of radium is trapped by the solid phase, while early diagenesis only induces a slight mobility of this radioelement. Highlights: The early diagenesis of long-lived radium isotopes 226 Ra and 228 Ra was evaluated in U-mining impacted granitic lake sediments. Ra activities in sediment pore waters were measured for the first time using very low background Germanium well detectors. 226 Ra and 228 Ra early diagenesis seem to be closely related to the reductive dissolution of iron oxyhydroxides. Calculated diffusive fluxes of Ra are significantly lower than those previously reported in Ra-enriched sediments.